Applying a PID-SMC synthetic control algorithm to the active suspension system to ensure road holding and ride comfort - Nguyen, Tuan Anh (PloS one, 2023)
Vehicle vibration has an essential effect on vehicle stability and smoothness. This article introduces a new solution to direct an active suspension system called the PID-SMC hybrid algorithm. In this work, a dynamic model is considered with external disturbances and parametric uncertainties. Besides, the design process of the hybrid controller is also clearly shown. Different from previous studies, this controller is built upon the synthesis of two component signals which are generated from two separate controllers. The error signals of the two-component controllers are derived from the results of the body displacement and acceleration measured by the sensors. A simulation process is done by the MATLAB software to evaluate the system’s quality. Two cases are used for the simulation, including four scenarios examined for each case. Based on the results obtained from the simulation and calculation technique, the acceleration and displacement values of a vehicle body were greatly decreased once the PID-SMC method was used, compared with the rest of situations. In the first case, the maximum value of the acceleration is only 0.54 (m/s 2 ), while the average value and the RMS value are 0.06 (m/s 2 ) and 0.07 (m/s 2 ), respectively. In the second case, the maximum value of vehicle body displacement is only 9.54 (mm), only 8.75%, compared to cars with only mechanical suspensions. Besides, the change in the dynamic load at the wheel is also relatively small. Therefore, the road holding and ride comfort of the automobile has been improved. In the near future, this algorithm will be combined with intelligent control algorithms to apply to many different types of random stimuli from the road surface.